Building Character Education with The History an Islamic Empires in Nusantara: A Theoretical Study - Zafri Zafri; Hera Hastuti; Zul ‘Asri (International Journal of Research in Counseling and Education, 2018)
Character is a basic value that builds individual personality. Character formation is influenced by genes or heredity and environment. The world of education, as one of the environments that shape individual personality is expected to have a maximum role in character formation. The importance of character studies is in response to moral decline, low ethics, lack of nationalism, and the emergence of instant generation. As a result, our generation easily violates the rules, not only the rules of society, and the rule of law but also the rules of religion. History learning is full of values, examples, patriotism, nationalism, and an unyielding spirit. One of the history learning materials in schools is the history of the Islamic kingdom in Nusantara. Resilience, tenacity and morality of Islamic leaders in building civilization and opposing western colonialism are real role model for students. Learning from experience, and the wisest learning is from the experience of people in the past (history).